2019
DOI: 10.1016/j.nmni.2019.100594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and molecular epidemiology of children with meningitis in Tehran, Iran: a prospective study

Abstract: The molecular epidemiology of meningitis in children is unclear in Iran, and data are scarce. We aimed to characterize its clinical and paraclinical features as well as to determine the distribution of genotype/capsular types of common bacterial meningitis agents in children in Iran. All children suspected to have meningitis aged 4 days to 15 years were enrolled onto a prospective cross-sectional study from January 2015 to September 2017. Diagnostic values of clinical features, cerebrospinal fluid and serum pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…There were more studies available on serogroup distribution from the EM region versus the NA region. Data were available from Iran (n = 2) [ 67 , 68 ], Kuwait (n = 1) [ 51 ], Qatar (n = 1) [ 69 ], Saudi Arabia (n = 6) [ 54 – 56 , 70 – 72 ], and Turkey (n = 8) [ 57 59 , 73 77 ], in the EM region (spanning 1987–2018), and from Egypt (n = 3) [ 61 , 78 , 79 ], Morocco (n = 6) [ 80 – 85 ], and Tunisia (n = 6) [ 64 , 86 – 90 ], in the NA region (spanning 1977–2019). Serogroups A, B and W were most frequently reported in the EM region, while B and C serogroups were most frequently reported in the NA region.…”
Section: Objective 2: Imd Epidemiologymentioning
confidence: 99%
“…There were more studies available on serogroup distribution from the EM region versus the NA region. Data were available from Iran (n = 2) [ 67 , 68 ], Kuwait (n = 1) [ 51 ], Qatar (n = 1) [ 69 ], Saudi Arabia (n = 6) [ 54 – 56 , 70 – 72 ], and Turkey (n = 8) [ 57 59 , 73 77 ], in the EM region (spanning 1987–2018), and from Egypt (n = 3) [ 61 , 78 , 79 ], Morocco (n = 6) [ 80 – 85 ], and Tunisia (n = 6) [ 64 , 86 – 90 ], in the NA region (spanning 1977–2019). Serogroups A, B and W were most frequently reported in the EM region, while B and C serogroups were most frequently reported in the NA region.…”
Section: Objective 2: Imd Epidemiologymentioning
confidence: 99%
“…Pormohammad et al reported 60% of the bacterial causes of meningitis in children in Tehran Hib (19).…”
Section: Discussionmentioning
confidence: 99%
“…Otros agentes infecciosos no son estudiados de manera rutinaria, ya sea por falta de recursos o por dificultades prácticas frente al envío y manejo de la muestra. (14) En la actual investigación, no fueron posibles los estudios establecidos nacionales e internacionalmente para el diagnóstico adecuado y tratamiento oportuno de las meningoencefalitis agudas coincidiendo con Dickinson F y colaboradores, (15) lo cual nos lleva a meditar y a tener en cuenta para posteriores estudios.…”
Section: Discussionunclassified